Woke : a young poet's call to justice - Browne, Mahogany L.; Acevedo, Elizabeth; Gatwood, Olivia (Roaring Brook Press, 2020)
Illustrated collection of twenty-four poems from three writers that expound on the theme of "woke"--being engaged in one's community and working towards greater equality and justice.